Study of neuropsychotropic properties of substance with neuroprotective activity dimeric dipeptide mimethic of human NGF, GK-2h - S. O. Kotelnikova; T. L. Garibova; T. A. Gudasheva; V. A. Kraineva; T. A. Voronina (Фармакокинетика и Фармакодинамика, 2016)
Dimeric dipeptide mimethic human nerve growth factor, bis-(N-monosucciniL-gLycyL-Lysine), GK-2h at doses 0,1, 0,5, 1,0, 1,5 mg/kg, i.p. has an antiamnesic effect on the modeLs of scopoLamine, maximaL eLectroshock or ketamin induced passive avoidance response amnesia. GK-2h at doses 1,0-1,5 mg/ kg possess weak antihypoxic und anticonvuLsive properties, it does not affect the expLoratory behavior of animaLs in the test of open fieLd.